Whey as Food-Grade Culture Medium on an Industrial Scale That Protects Probiotics During In Vitro Digestion - Bauer Estrada, Katherine; Caldas Abril, Miguel; Bonilla Bravo, Valentina; Ruiz, Monica; Quintanilla-Carvajal, María Ximena (Frontiers in Food Science and Technology, 2022)
Production of probiotics at industrial scale to be used as food supplements involves diverse kinds of processes such as selection of microorganisms, 2) fermentation, 3) drying, and the use of non-food grade commercial culture mediums that should be washed after obtaining the ideal cell concentration. Then, food grade culture medium for probiotics that do not need to be washed and protect the microorganisms through the gastrointestinal tract, is proposed as a low-cost alternative to grow probiotics to be used for incorporation in food. In this way, an experimental design was carried out to obtain the operative conditions for spray drying food-grade culture medium at industrial scale. The factors evaluated were the inlet and outlet temperature and a specific heat treatment before the drying process. As response variables the physical properties of the food-grade medium in powder and the viability count of the probiotic Limosilactobacillus fermentum K73 were evaluated. The viability of four different known probiotics (Limosilactobacillus fermentum, Lactobacillus delbruekii, Lacticaseibacillus rhamnosus and Enterococcus faecium) was proved which resulted after 10 h in 10.6, 10.2, 10.1, and 11.2 logCFU/ml, respectively. Also, in vitro digestions of the probiotics in this food-grade medium were carried out and compared with digestions of the probiotics in the commercial medium MRS, demonstrating that the proposed medium protect the probiotics of the gastrointestinal conditions, allowing them to arrive at the intestine at 7.3, 6.8, 7.5 and 7 logCFU/mL, for L. fermentum, L. delbruekii, L. rhamnosus and E. faecium, respectively. Finally, the optimal conditions of the spray drying process were used to reproduce the whey food-grade medium at a large-scale spray dryer (dimensions), this to validate the medium performance in the production of powdered probiotics as L. fermentum.